2015
DOI: 10.1016/j.immuni.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Sequence Signal 3 Paralyzes Primary CD4+ T-Cell-Dependent Immunity

Abstract: Summary Primary T cell activation involves the integration of three distinct signals delivered in sequence: 1)antigen recognition, 2)costimulation, and 3)cytokine-mediated differentiation and expansion. Strong immunostimulatory events such as immunotherapy or infection induce profound cytokine release causing “bystander” T cell activation, thereby increasing the potential for autoreactivity and need for control. We show that during strong stimulation, a profound suppression of primary CD4+ T cell-mediated immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 38 publications
1
66
1
Order By: Relevance
“…As we have discussed, over-activation of inflammatory mechanisms by adjuvants can lead to adaptive immune suppression 140,141 , requiring additional intervention such as inhibition of IDO 105 . Adaptive immunity requires a critical sequence of signals and any deviation in the appropriate timing and degree of inflammation has the potential to limit antigen-specific immunity 173 . The appropriate timing of adjuvant delivery in relation to radiation needs to be determined in order to ensure the success of this approach 174 .…”
Section: Resultsmentioning
confidence: 99%
“…As we have discussed, over-activation of inflammatory mechanisms by adjuvants can lead to adaptive immune suppression 140,141 , requiring additional intervention such as inhibition of IDO 105 . Adaptive immunity requires a critical sequence of signals and any deviation in the appropriate timing and degree of inflammation has the potential to limit antigen-specific immunity 173 . The appropriate timing of adjuvant delivery in relation to radiation needs to be determined in order to ensure the success of this approach 174 .…”
Section: Resultsmentioning
confidence: 99%
“…Sorting purified memory and na€ ıve CD4C and CD8C T cells revealed that the CD4C na€ ıve T cell compartment was completely paralyzed even to anti-CD3 and anti-CD28 or mitogen stimulation. 6 It was also noted that this paralysis occurred during systemic LPS administration. Microarray analysis indicated that suppressor of cytokine signaling-3 (SOCS3) was induced during the immunotherapy regimens in the CD4C T cells.…”
Section: Signal 3 Alone Paralyzes Na€ ıVe Cd4c T Cell Responsesmentioning
confidence: 95%
“…4,5 The vast majority of studies thus far have focused on the impact of Signals 1 and 2. However, the role of Signal 3 alone on T cell function, particularly with regard to na€ ıve T cells, has remained elusive until the recent studies by Sckisel et al and Urban et al 6,7 Signal 3 alone results in antigen-nonspecific memory T cell expansion There are critical differences between cell surface molecules of na€ ıve and memory T cells with regard to the IL2 receptor complex subunit expression. The high affinity receptor complex to IL2 consists of 3 subunits: CD25, CD122 and CD132.…”
Section: Factors Impacting Primary Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a variety of immune cells that target SLOs in a context-dependent fashion participate to the primary perception of contextual signals and provide part of the primary response to such signals. These include notably Treg and Breg cells irrespective of their antigen specificity 27, 28 , NK cells 29 , polymorphonuclear cells 30 , monocytes 31, 32 , innate lymphoid cells 33, 34 as well as naive T or B lymphocytes 35, 36 . Overall, the primary perception of contextual signals is a cooperative task performed by a large array of cell types that reside in SLOs or migrate toward SLOs.…”
Section: Introductionmentioning
confidence: 99%